Cooperative research– on collective fieldnotes, experience negotiation and common text - Gańko, Anna; Łątkowski, Mikołaj (Journal of Education Culture and Society, 2019)
Aim.  The aim is to depict specificy of fieldnotes  as a first result of research experience are standing between perception which obviously has to be personal (even if it's based on non-individual experience) and text which main feature is to be intersubjectively understandable.Method. The study is based on experience of conducting collaborative fieldwork and writing common fieldnotes. Paper itself is also an example of collaborative work - written together is an opportunity to share theoretical perspective on team research grounded in fieldwork experience in process.Resullt and Conclusions. Fieldnotes as a part of fieldwork process are first step of translation from subjective experience to objective knowledge. In the case of collaborative writing, unlike in the case of report where the final research result is presented which can have the form of general, conclusion, fieldnotes are much more dynamic – become domain of negotiation revealing crucial points of collective fieldwork experience.